Application of the Project Based Learning (PjBL) Model through Making Tempe to Improve Student Learning Outcomes and Creativity - Puja Setiawan; Wahidin; Asep Ginanjar Arif (Global Writing Academica Researching and Publishing, 2023)
The aim of the research is to examine implementation, increase in learning outcomes, student creativity and student responses to Project Based Learning (PjBL) learning in making tempe. This type of research is quasi-experimental, with a non-equivalent control group design. The population of this study were all 9th ​​grade students of SMP Darussalam Cimanggu and the samples were taken from two classes using the saturated sample technique. The experimental class was given the PjBL model treatment and the control class was treated with a scientific approach. The instruments used were observation sheets, cognitive learning outcomes tests, and student response questionnaires. The results showed that the implementation of the PjBL model was well implemented, marked by the implementation of the PjBL model by teachers, with an average of 91.6% in the very good category. The achievement of the experimental class in learning outcomes and student creativity was better based on the significance hypothesis test 0.031 < 0.05, the initial hypothesis was rejected indicating that there were differences in student learning outcomes and creativity. The learning process of implementing PjBL through making tempe shows > 80% of students responding positively to having an impact on creativity and student learning outcomes increasing because learning is more creative, innovative, and fun so that learning is in favor of students.